The Androgynous Ideal in Angela Carter’s The Passion of New Eve - Fizra Sattar; Sohail Ahmad Saeed; Noveen Javed (International Journal of Psychosocial Rehabilitation, 2020)
The present study is an analysis of the gender constraints, and the limitations of living in a gendered society. It uses Carter’s The Passion of New Eve as the primary text to explore the restrictive nature of the gender dynamics. As western society provides two opposing experiences for masculinity and femininity in the society, gender becomes political issue. Carter’s work is a contemplation of the said issues. Using feminism as the primary theory, this study centres itself to explore Carter’s vision and brings out the imbalanced gender hierarchy of the society as is present in The Passion of New Eve. Since the 1970’s, fantasy has offered an exuberant expansion which has facilitated female authors equally to condemn the present societal exercises and to contemplate on unusual social classifications. Angela Carter’s The Passion of New Eve embodies, relative to this exact standpoint, an inventive and pioneering reconstruction of feature feminine and masculine patterns. Carter eliminates and deconstructs the gender peripheries amid man and woman. Regardless of one’s gender and at times because of that, one can turn into the prey or the predator. A dominating male can never under any circumstances understand the oppression and violation a female endures until or unless he himself go through that same ordeal.